Acción del boro, zinc calcio y otros micronutrientes en las fases fenológicas de floración y cuajado de mazorcas en cacao nacional sitio Jumón - Córdova Sotomayor, Richard Fernando (2011)
In the Farm San Luis located in the place Jumón, Santa Rosa city, province of “El Oro”, in a plantation of national cocoa itself study the answer of this cultivation to the application of boron, calcium, zinc and other micro nutrients after the phytosanitary pruning. The objectives presented were: Testing the efficiency of four levels of boron in combination with zinc, calcium and other micro nutrients applied in national cocoa in production by means of evaluation in regular form, each 15 days since the pruning; y, establishing the most appropriate dose than permitting to assure the flowering and jelled of cobs in the plantation. The area had an average annual temperature of 24.4 º C, average annual rainfall of 624 mm. Dry climate without excess water, mega heat or warm. . According to the natural life zone Holdridge is classified as dry forest formation - Tropical (bms-T).The processing applied to trees pruned was: boron in concentrations of 150, 300 and 450 ppm, calcium (100ppm), zinc (437 ppm) and cobalt (500 ppm). Treatments were applied to national cacao plants, distributing the following treatments on the basis of randomized block design with three replications, totaling 12 experimental units. The variables analyzed were: growth of bud, days to the flowering, number of bearings by main branch, number of flowers by bearing, number of flowers jelled by bearing, number of fruits by plant and registration of temperature and precipitation.The variety of national cocoa responded to the application of Boron with dose from 150 and 450 ppm; The boron influence in the growth in length of the bud, the number of floral bearings, flowers jelled and cobs to the crop, surpassing the witness. In the cobs weight evaluation to the crop and weight of the almonds, himself he was not found significant answers.